The direct and indirect spatial spillover effects of infrastructure on urban green and smart development - Wang, Dandan; Xu, Lingyan; Du, Jianguo (Frontiers in Environmental Science, 2023)
Economic development is not simply the accumulation of elements, but the improvement of efficiency, which is supported by infrastructure construction. In particular, the green and smart urban development (UGSD) in recent years has put forward higher requirements for infrastructure, and domestic trade as well as opening-up are of great significance during the process. Based on the panel data of 221 prefecture-level cities in China from the year of 2005 to 2019, this paper adopts the undesirable SBM model and GML index to measure the level of UGSD. Then the spatial Durbin model is conducted to explore the direct spatial spillover effects and the spatial decomposition effects of energy, transportation, and information infrastructure on UGSD. Considering the context of dual cycle, the indirect effects of domestic trade and opening-up between infrastructures and UGSD are further analyzed. Results show that UGSD demonstrates strong spatial agglomeration and maintains a stable spatial positive correlation with different spatial matrices. In general, energy and transportation infrastructure show positive spatial spillover effects on UGSD. By contrast, information infrastructure presents positive spatial spillover effect on UGSD on the whole, while shows insignificant and negative spatial spillover effect with geographical distance matrix. Furthermore, the mediation effect indicates that both transportation and information infrastructure mainly promote local and adjacent cities' UGSD through domestic trade with economic distance matrix. By contrast, energy infrastructure exerts positive spatial spillover effect on UGSD through weakening the negative impact of opening-up. The conclusions of the research show that it is necessary to construct infrastructure in a reasonable way, strengthen the positive spillover effect of intercity factors, and promote the two-wheel driving effect of domestic trade and opening-up on the relationship between infrastructure and UGSD.